The Elderly and Holy Communion: The Understanding of the Elderly at GBKP Berandan about the Sacrament of Holy Communion as a Critical Reflection on the Sacrament of Holy Communion GBKP - Melkisedek Sembiring; Bayu Kaesarea Ginting; Asnewastri Asnewastri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The elderly is someone who has reached the age of 60 years and over. In general, the elderly experiences a sense of contradiction between satisfaction and hopelessness. The elderly feels satisfied if they believe that they have lived life and went through the previous phases well and are able to accept the aging process. However, they can despair, if they find themselves a failure in the past. There are elderly people who think they are useless along with the decline in physical function and health that makes them unable to carry out activities as usual. In addition, the elderly may feel that they are not cared for, experience loneliness, and even suffer from post power syndrome. On the other hand, the elderly have life experience, free time, and in society are respected as parents. The experience of the elderly meeting bread and wine, as symbols of the body and blood of Jesus in Holy Communion, makes the elderly more refreshed, strong, excited and not worried about life. The elderly also experiences strengthening, peace, and joy in attending Holy Communion. Based on initial interviews with four elderly people at GBKP Berandan, there was an impression that the elderly had difficulty explaining their understanding of the sacrament of Holy Communion at GBKP. However, if it is associated with the symbols of bread, wine, and singing in the sacrament of Holy Communion, the elderly is able to understand Holy Communion at GBKP. Based on this phenomenon, the presenter is interested in conducting research entitled "Elderly and the Holy Communion: Understanding the Elderly in GBKP Homen About the Sacrament of Holy Communion as a Critical Reflection on the Sacrament of Holy Communion GBKP". I base this paper on Erik Erikson's perspective on psychosocial development and Richard H. Gentzler's perspective on lasia, then John Calvin's perspective on Holy Communion and Gordon W. Lathrop's perspective on experiencing meaning through encounters with liturgical symbols.